Self-Perceived Psychophysical Well-Being of Young Competitive Swimmers With Physical or Intellectual Impairment. Issue 5 (October 2019) - Puce, Luca; Marinelli, Lucio; Girtler, Nicola G.; Pallecchi, Ilaria; Mori, Laura; Simonini, Marina; Trompetto, Carlo
Regular practice of sport activities yields psychophysical benefits for both the general population and persons affected by physical or intellectual impairments. Practicing competitive sport may add further value to these benefits. The objective of this observational cross-sectional study was to investigate the role of competitive sport practice in enhancing self-perceived psychophysical well-being of some select participants, using the Psychological General Well-Being Index and the Short Form-12 indices. We recruited at national events 100 young Italian competitive swimmers affected by physical or intellectual impairment. These respondents' results were compared with those of a control group of 100 Italian participants who did not practice competitive sport but who were also affected by physical or intellectual impairment, randomly selected from rehabilitation clinics and communities of young people with disabilities. Scores of psychological and emotional well-being were higher by 40% or more for the practitioners of competitive sport ( p  < .0001; Cohen's effect size d  ≥ 1.3). While our study's results suggest possible positive psychophysical benefits to competitive sport practice for young people affected by physical or intellectual impairment, longitudinal research is needed to be certain that our results are not due to self-selection into sports participation of those persons with disabilities who have a uniquely higher sense of well-being.